2000
DOI: 10.1074/jbc.m005033200
|View full text |Cite|
|
Sign up to set email alerts
|

Time-resolved Infrared Spectroscopy Reveals a Stable Ferric Heme-NO Intermediate in the Reaction of Paracoccus pantotrophus Cytochrome cd 1 Nitrite Reductase with Nitrite

Abstract: Cytochrome cd 1 is a respiratory enzyme that catalyzes the physiological one-electron reduction of nitrite to nitric oxide. The enzyme is a dimer, each monomer containing one c-type cytochrome center and one active site No kinetically competent release of NO could be detected, indicating that at least one additional factor is required for product release by the enzyme. Implications for the mechanism of P. pantotrophus cytochrome cd 1 are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
84
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(93 citation statements)
references
References 36 publications
6
84
3
Order By: Relevance
“…Nitrite or nitric oxide was bound to the d 1 heme, and His/His coordination of the c heme was observed. In contrast, rapid reaction solution studies, reacting reduced wild type cytochrome cd 1 with nitrite, showed no evidence of His/His coordination of the c heme but only His/Met coordination (24). It is possible, in light of the results presented here, that the same switching of ligands occurred in the nitrite-soaked crystals as proposed here for the Y25S cytochrome cd 1 crystals.…”
Section: Visible Absorption Spectroscopy-contrasting
confidence: 50%
“…Nitrite or nitric oxide was bound to the d 1 heme, and His/His coordination of the c heme was observed. In contrast, rapid reaction solution studies, reacting reduced wild type cytochrome cd 1 with nitrite, showed no evidence of His/His coordination of the c heme but only His/Met coordination (24). It is possible, in light of the results presented here, that the same switching of ligands occurred in the nitrite-soaked crystals as proposed here for the Y25S cytochrome cd 1 crystals.…”
Section: Visible Absorption Spectroscopy-contrasting
confidence: 50%
“…2 A and B) is thus representative of two processes, namely evolution of the initial mixture to the steady state and formation of the dead-end species. An overall scheme showing the various possible intermediates, as well as information obtained by George et al (20), is depicted in Fig. 3 and detailed in the figure legend.…”
Section: Resultsmentioning
confidence: 99%
“…Simple pre-reduction of the enzyme has also resulted in much higher k cat values than could be obtained with the oxidized (as prepared) enzyme for any of the electron donor proteins: cytochrome c 550 , pseudoazurin, or horse heart cytochrome c, in combination with any of the three known electron acceptors, nitrite, oxygen, or hydroxylamine (3,13). Cytochrome cd 1 can act as an oxidase; and in the early stages of this reaction an oxidized state of the protein with His/Met coordination at the c-type cytochrome center has been observed (10,15), as was also the case for a form of the enzyme seen after a 1-electron oxidation of cytochrome cd 1 by nitrite (5). His/Met coordination of the heme of the c domain in the oxidized state is also found in solution for both the semi-apo form of the protein that has lost the d 1 heme (15) and the c domain expressed in isolation (16).…”
mentioning
confidence: 99%